Growing groups, cooperation, and the rate of entry - Eva Ranehill; Frédéric Schneider; Roberto A. Weber (University of Zurich, Department of Economics, 2013)
We study the stability of voluntary cooperation in response to varying group growth rates. Using a laboratory public-good game, we construct a situation where increasing group size yields potential efficiency gains, but only with sustained cooperation. We then study the effect of exogenously varying growth rates on cooperation. Slow growth yields higher cooperation rates and welfare than fast growth, both for incumbents and entrants, which is consistent with optimistic self-reinforcing beliefs persisting under slower growth. Allowing incumbent group members to select growth rates also sustains high cooperation rates, but growth stalls at intermediate group sizes, leaving potential efficiency gains unrealized.
Keywords: C92; C72; 330; voluntary cooperation; experiment; public good game; Öffentliche Güter; Allokation; Kooperation; Nichtkooperatives Spiel; Test; Theorie